Well, what about intraspecific variation? Taxonomic and phylogenetic characters in the genus Synoeca de Saussure (Hymenoptera, Vespidae) - Carpenter, James M.; Andena, Sergio R.; Noll, Fernando B.; Wenzel, John W. (Zootaxa, 2013)
Cely and Sarmiento (2011) took issue with the cladistic analysis of relationships among species of the genus Synoeca by Andena et al. (2009a), and presented a reanalysis. They claimed that intraspecific variation in the genus is meaningful, and proper consideration yields a conclusion different from that of Andena et al. Both their critique and reanalysis are vitiated by numerous errors, as is shown in the present paper.